Gum Arabic containing Allium sativum L. essential oil-based nanoparticles as biofumigant grain protectant against Callosobruchus maculatus F. - Huda H. Elbehery; Habiba A. Ahmed; Samar Sayed Ibrahim; Waleed Abouamer; Amr Farouk (PLoS ONE, 2025)
Gum Arabic nanoparticles (GA NPs) were used to nano-encapsulate Allium sativum or garlic essential oil (GO) using the freeze-drying technique. The fumigant toxicity of GO and GO-GA nanoparticles was evaluated against Callosobruchus maculatus , a major pest of stored products. Adults were exposed to concentrations of 10.0, 5.0, 2.5, and 1.25 µL/L air for 24 hours to evaluate the lethal concentration (LC) values. Gas Chromatography-Mass Spectrometry for GO identified diallyl trisulfide (38.78%), allyl methyl trisulfide (23.93%), and diallyl disulfide (13.66%) as the main compounds. Dynamic light scattering and transmission electron microscope tests verified the stability and uniformity of the produced nanoparticles, which were distinguished by their small particle size (15.10 nm), low PDI value (0.31), and negative zeta potential (−10.20). A high encapsulation efficiency of 84.74 ± 1.74% was achieved for the produced nanoparticles. The linkage and interaction between GO and GA as a polymer were confirmed by Fourier transform infrared spectroscopy. After 24-hour exposure, GO-GA NPs resulted in lower LC 50 values (1.14 µL/L air) than GO (2.08 µL/L air) against C. maculatus adults. The inclusion of GO-GA NPs at LC 40 had a significant post-effect on progeny production of C. maculatus , resulting in a significant reduction in the number of deposited eggs and adult emergence, which led to a significant decrease in the percentage of adult emergence to 15.23 ± 5.46 compared to 61.33 ± 2.94, as observed in the GO treatment. GO-GA NPs enhanced the persistence activity, exhibiting a continued toxic effect for >30 days, with a PT 50 of 22.29 days compared to 12.79 days for GO. This study suggested that nano-formulation could enhance the efficiency of garlic oil as an eco-friendly grain protectant to control C. maculatus adults.